1989
DOI: 10.1037/0022-3514.57.4.590
|View full text |Cite
|
Sign up to set email alerts
|

Enough said: Three principles of explanation.

Abstract: Four studies demonstrated that explanations of interpersonal experiences generally conform to three principles: (a) Implicit causality-Explanations should refer to the stimulus person rather than the experiencing person; (b) cognitive balance-Something positive should be said if the experience is positive and something negative should be said if the experience is negative; and (c) imbalance repair-supplementary statements designed to correct unsatisfactory explanations should be proportional to the size of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 33 publications
2
38
0
Order By: Relevance
“…This raises important questions for theories of language and reasoning, as only the consistency theory is able to explain why people will draw a positive conclusion in one case and a negative conclusion in another case, even though both cases appear to convey the same expected utility of doing the consequent given the antecedent. Our results complement findings on causal explanation which demonstrate the operation of polarity (Majid, Sanford, & Pickering, 2006) and balance (Brown & van Kleeck, 1989;Rudolph & von Hecker, 2006), suggesting that the consistency approach can provide general organising principles to subsume a range of linguistic and world knowledge effects in reasoning.…”
Section: General Discussion and Conclusionsupporting
confidence: 85%
See 1 more Smart Citation
“…This raises important questions for theories of language and reasoning, as only the consistency theory is able to explain why people will draw a positive conclusion in one case and a negative conclusion in another case, even though both cases appear to convey the same expected utility of doing the consequent given the antecedent. Our results complement findings on causal explanation which demonstrate the operation of polarity (Majid, Sanford, & Pickering, 2006) and balance (Brown & van Kleeck, 1989;Rudolph & von Hecker, 2006), suggesting that the consistency approach can provide general organising principles to subsume a range of linguistic and world knowledge effects in reasoning.…”
Section: General Discussion and Conclusionsupporting
confidence: 85%
“…Existing research confirms that causal world knowledge plays a role in making a sentence seem normal or "bizarre". Thus research (Brown & van Kleeck, 1989;Rudolph & von Hecker, 2006) has shown that people judge "imbalanced" sentences such as John admires Mary because she is so arrogant as more "bizarre" than balanced sentences such as John admires Mary because she is so friendly. This can be interpreted as a sentence directionality effect insofar as a positive emotion (admiration) should normally be evoked by a positive quality (e.g., friendliness).…”
Section: Sentence Directionality: a Consistency-based Approach To Pramentioning
confidence: 95%
“…We interpret this as the balanced triads "making sense" more than unbalanced trials and therefore seeming more coherent than unbalanced triads (see Brown & van Kleeck, 1989;Crandall, Silvia, N'Gbala, Tsang, & Dawson, 2007;Rudolph & von Hecker, 2006) which, in turn, translated into greater 'proximity', that is, the constituent elements within balanced triads showed shorter distances between each other than the constituent elements within unbalanced triads. In terms of the SDT analysis, this main result corresponds to finding stronger response tendencies in the no fit direction for balanced than unbalanced relations, independent of how well the objective fit and no fit could be discriminated for balanced versus unbalanced materials.…”
Section: Discussionmentioning
confidence: 99%
“…we know from earlier research that participants usually perceive balanced social triads as making more sense than unbalanced (Brown & Van Kleeck, 1989;Crandall et al, 2007;Rudolph & von Hecker, 2006), whereas in the syllogism case (Experiments 2a and 2b) participants were given formal training to evaluate categorical syllogisms and were asked to think about the validity of each syllogism immediately prior to the spatial task, and immediately afterwards to make a judgment on validity (which was reasonably accurate on average, see Table 4). Finally, in the latent causality case coherence is thought to be achieved by a participant's own, schema-guided, re-constructive activity (see Bartlett, 1932).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation